2019
DOI: 10.2166/washdev.2019.059
|View full text |Cite
|
Sign up to set email alerts
|

Underrepresented groups in WaSH – the overlooked role of chemical toxicants in water and health

Abstract: The anthropogenic release of chemicals from industry, agriculture and the breakdown of consumer wastes constitute a major threat to water resources and public health. Pollution is severe and increasing in the developing world where chemical substances are produced, used, and disposed of in an unregulated manner. The global public health consequences of chemical pollution are comparable to or greater than those of widespread infectious diseases such as HIV/AIDS, tuberculosis, and malaria. However, chemicals hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…It is possible, or perhaps likely, that exposure to chemical immunotoxins bears significant responsibility for the failure of traditional WASH interventions to achieve reductions in diarrheal disease (J. Kearns, 2019; J. P. Kearns, Bentley, et al, 2019). Furthermore, given known effects on the developing fetus, chemical immunotoxin exposure could also partly explain why no or only slight reductions in stunting after nutrition and nutrition-plus-WASH interventions were observed in the large trials (J. Kearns, 2019; J. P. Kearns, Bentley, et al, 2019).…”
Section: Moving Towards Transformational Washmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible, or perhaps likely, that exposure to chemical immunotoxins bears significant responsibility for the failure of traditional WASH interventions to achieve reductions in diarrheal disease (J. Kearns, 2019; J. P. Kearns, Bentley, et al, 2019). Furthermore, given known effects on the developing fetus, chemical immunotoxin exposure could also partly explain why no or only slight reductions in stunting after nutrition and nutrition-plus-WASH interventions were observed in the large trials (J. Kearns, 2019; J. P. Kearns, Bentley, et al, 2019).…”
Section: Moving Towards Transformational Washmentioning
confidence: 99%
“…A small number of studies have underscored the importance and treatability of chemical contaminants in WASH (J. P. Kearns, Bentley, et al, 2019; J. P. Kearns, Knappe, & Summers, 2014; J. P. Kearns, Shimabuku, Mahoney, Knappe, & Summers, 2015). Recently it was suggested that chemical exposures that were not accounted for could partly explain the null results obtained in the WASH Benefits and SHINE trials (J.…”
Section: Moving Towards Transformational Washmentioning
confidence: 99%
“…Appropriate technologies are essentially considered as interim solutions wherever a centralized water supply is not yet available 1 . Factors relevant for selecting an appropriate solution for safe drinking water supply include 1 , 7 , 8 : (i) Simplicity in operation (no special skilled personnel), (ii) robustness (no frequent break downs), (iii) affordability (low installation and operation costs), (iv) ability to function without electricity, and (v) use of local skills and readily available resources. Research during the past two decades has rediscovered filtration systems based on metallic iron (Fe 0 ) as an affordable, applicable, and efficient water treatment technology for decentralized water supply (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These impacts are expected to substantially increase in the coming decades due to: (1) increased urbanization, (2) increased industrialization, and (3) climate change 1 3 . The low-income communities who are spatially scattered, and economically disadvantaged are most impacted by water pollution or lack of safe drinking water 2 4 . Thus, low-income communities need affordable, efficient and applicable technologies for their drinking water supply.…”
Section: Introductionmentioning
confidence: 99%